Antifungal activity of Aniba canelilla (Kunth) Mez essential oil and its main compound 1-nitro-2-phenylethane against dermatophytes - Kreutz, Tainá (2024)
The essential oil of Aniba canelilla (Kunth) Mez (EOAC), an Amazon plant composed of a rare nitro compound, has shown scientific evidence of antifungal activity but is still unexplored against dermatophytes. The antifungal susceptibility of EOAC and its main compound, 1-nitro-2- phenylethane (NP), was evaluated against dermatophytes (Trichophyton rubrum, T. mentagrophytes and Microsporum canis), evidencing antifungal activity with an inhibitory concentration lower than 256 μg/mL. The mechanism of action was also evaluated, and it is suggested that EOAC and NP have fungicidal action in the fungal membrane, since the antifungal activity occurs through a modification of the shape of the conidial structures of the fungus, showing the permeability of the intracellular content due to the visually observed plasmolysis and cytosolic extravasation through an osmotic process. These results suggest the essential oil and its main compound are promising plant-derived alternatives for treating ungual dermatophytosis.